Ambient Air Pollution Exposure and Social Health Outcomes in Communities Near the Kawatuna Landfill, Palu, Indonesia - Saifah, Andi; Ardiputra, Muh. Akbar; Miswan, Miswan; Safirah, Nur Annisa; Arifuddin, Adhar; Guli, Musjaya; Parmin, Parmin (Journal of Health and Nutrition Research, 2025)
Communities living near landfill sites are often exposed to high levels of ambient air pollution, which may impact their physical and psychosocial health. This study aims to explore the relationship between ambient air pollution exposure, particularly carbon monoxide (CO) and nitrogen dioxide (NO₂), and the social health outcomes of communities residing near the Kawatuna Landfill in Palu, Indonesia. A cross-sectional study involving 143 respondents was conducted using structured interviews and environmental exposure assessments. Correlation analyses, Mann-Whitney U tests, and regression models were applied to examine the relationships between air pollution exposure and respiratory disorders, smoking behavior, stress levels, and social interaction. The findings revealed a significant positive correlation between CO and NO₂ exposure and stress levels (r=0.217, p = 0.022), although the relationship was weak. No significant associations were found between air pollution exposure and smoking behavior, social interaction, or respiratory disorders in multivariate analyses. The Mann-Whitney U test indicated that individuals with respiratory disorders were exposed to higher levels of CO and NO₂ (p = 0.038). Ambient air pollution exposure in this community is more closely related to psychosocial stress than to physical health behaviors or social interaction. Community-based health interventions should consider the cultural context and perceived environmental risks to effectively promote health in such vulnerable populations.